Reforms and identities: How relentless pursuit of improvements produces a sense of helplessness among bureaucrats. Issue 2 (10th April 2017) - Glinka, Beata; Hensel, Przemyslaw G.
Abstract : Purpose: The purpose of this paper is to show how the identities of the employees of Polish public administration are shaped in the process of public system reforms. Design/methodology/approach: The findings are based on interviews with 40 employees of the Polish public administration. The authors have used open interviews as well as projective methods to discover and explore beliefs and attitudes of bureaucrats towards their work and the system of public administration. The selected sample was diversified both spatially and systematically to reflect the diversity of organisations that constitute the Polish public administration system. Grounded theory was used for data coding and interpretation. Findings: The study indicates that organisational change initiatives designed to enhance the quality and efficiency of public administration may have negative impacts on the identities of public servants and may lead to their increased incapacity. Rather than sparking entrepreneurial behaviours and transforming bureaucrats into managers, introduction of the rhetoric of New Public Management and New Public Governance in the Polish public administration has contributed to strengthening of classical dysfunctions of bureaucracy. Research limitations/implications: The results imply that the understanding of organisational changes in the Eastern European public sector – which are usually studied through the lenses of regulation and economy – would benefit from more sociologically and historically oriented studies. The limitations of our results are associated with the adopted qualitative subjective methodology. Practical implications: Foreign-born templates of reforms may appear to be logical and coherent but they rest on certain assumptions about identities and value structures that are not necessarily congruent with the identities at the adoption site. For that reason, successful reform projects need to consider and problematise the content and shape of culturally conditioned identities. Social implications: Understanding of public sector reforms' implication should lead to the improvement of change programmes as well as to the evolution of public administration towards a form more desired by the society. It is especially important as Polish society considers public administration as one of factors influencing (in a negative way) the quality of life. Originality/value: The paper provides insight into public administration reforms in Poland and their impact on public servants' identities.